Relationship between knowledge and recognition of sexually transmitted infections and sexual behaviour in young people who provide the military in a depart ment of Peru - Rocío Anani Adriazola Flores (2019)
The increase in cases of sexually transmitted infections (STIs) in adolescents is increasing. For the study were selected youngsters who did their military service in 2008 and the aim was to relate their knowledge of ST1s with Sexual Behavior. The questionnaire was administered by Dr. Alba to 72 young people and the results were: 63.9% of the population was 18, 19.4% 17 years 54.2% 45.2% were men and women. The 62.5% felt that condoms do not protect most, 19.4% said that if it protects. On Sexual Behavior 55.6% reported having had more than one sexual partner for a year. The relationship is statistically significant among the variables Number of Sexual Partners and presence of an STI. Finally it was concluded that the population has adequate knowledge of STI but sexual behavior is risky (not always use condoms during sexual intercourse).